Security protection of neighborhood area networks in smart grid systems - Hu, Ankang (2016)
As the smart grid technologies come into practice, the wireless mesh networks with EMSA security protocols are fast developing to keep pace of the next generation electricity grid system. The EMSA security protocols provide security guarantee for the communication process in wireless mesh networks. EMSA was first proposed in IEEE 802.11s standard in July, 2011. Since then, several strategies and algorithms were put forward to improve the performance of EMSA security protocols. One of these is the dynamic updating key strategy raised by Junguo Liao and Mingyan Wang. Although this proposal improved the efficiency performance of the EMSA security protocol, it still has the problem of lack of protection mechanism. In the project, we analyze the threats and attacks in the dynamic key updating strategy based on EMSA and make some modification for it, in order to make it perform better under high attack probability situation. In the end, we use the CSP module in PAT to verify the security protocol and simulate it in MATLAB.